Amerigo Filia (1873-1925) and the first School of Pediatrics in the island of Sardinia - Maria Grazia Clemente; Patrizia Cincinnati; Luigi Cataldi; Roberto Antonucci (Hygeia Press di Corridori Marinella, 2021)
Amerigo Filia was born on July 18, 1873, in Sassari, Sardinia, Italy. After attaining his Medicine degree at the University of Turin in 1900, he went to Rome to study Pediatrics at the School of Pediatrics directed by Professor Luigi Concetti. His academic career began in Sassari when he was appointed as teacher of Pediatrics in 1911, becoming Full Professor in 1917, Dean of the School of Medicine and Surgery in 1918 and, finally, Rector of the University in 1919. He distinguished himself as the founder of the Pediatric Clinic and the School of Pediatrics in Sassari, both being the first ones in Sardinia, and as the promoter of the restoration of the front of the main building of the University of Sassari ("Palazzo dell'Università"), as well as of new buildings to host Scientific Institutes and Clinics. Moreover, in 1923, he succeeded in preventing the suppression of Sassari University as a consequence of the "Gentile" reform. As documented by his scientific publications, Filia's research activity included both experimental and clinical studies focusing on the renal excretion of high dose of arsenic, the effects of Lactobacilli in infantile enteritis, as well as on renal tuberculosis and pulmonary echinococcosis in children. Amerigo Filia died suddenly on December 21, 1925, in Rome, where he was participating in a university competition as a committee member.